The Fragile Bonds of Kinship: Analysing Sibling Relationships in Anita Desai’s Clear Light of Day (International Journal of Environmental Sciences, 2024)
Anita Desai's Clear Light of Day examines the fragile bonds of sibling relationships within the Das family, against the decaying backdrop of Old Delhi. By juxtaposing contrasting approaches to responsibility and aspirations, Desai portrays how shared history and unspoken grievances shape kinship. Central to the narrative are themes of caregiving and sacrifice, embodied in Bim’s steadfastness and Tara’s guilt-laden escape. Baba’s emotional inertia and Raja’s ideological divergence further accentuate the disintegration of familial bonds, mirroring the socio-political ruptures of Partition-era India. Aunt Mira’s overlooked yet pivotal role adds depth to the caregiving motif, highlighting the burdens borne silently. Through a nuanced exploration of these relationships, this paper explores the universal struggles of kinship in a changing socio-political landscape, emphasizing the enduring tensions between love and estrangement within families.